Italy - Dean, Jessica, 1963- (Minneapolis, MN : Pogo, 2019)
Explores the country of Italy, including its climate, culture and features.
School Library Journal, November 2018
Includes index.
2.4
K-3
540L
Keywords: Italy -- Juvenile literature; Italy; Readers (Elementary) -- Nonfiction